Organic Sunscreens—Is Their Placenta Permeability the Only Issue Associated with Exposure During Pregnancy? In Silico Studies of Sunscreens’ Placenta Permeability and Interactions with Selected Placental Enzymes - Anna W. Sobańska; Andrzej M. Sobański (Molecules)
One of the functions of placenta is to protect the fetus against harmful xenobiotics. Protective mechanisms of placenta are based on enzymes, e.g., antioxidant enzymes from the glutathione S-transferases group (GST) or human N-acetyltransferase 2 (NAT2). Many organic sunscreens are known to cross biological barriers—they are detected in mother’s milk, semen, umbilical cord blood or placental tissues. Some organic sunscreens are able to cross the placenta and to interfere with fetal development; they are known or suspected endocrine disruptors or neurotoxins. In this study, 16 organic sunscreens were investigated in the context of their placenta permeability and interactions with gluthatione S-transferase and human N-acetyltransferase 2 enzymes present in the human placenta. Binary permeability models based on discriminant analysis and artificial neural networks proved that the majority of studied compounds are likely to cross the placenta by passive diffusion. Molecular docking analysis suggested that some sunscreens show stronger affinity for glutathione S-transferase and human N-acetyltransferase 2 that native ligands (glutathione and Coenzyme A for GST and NAT2, respectively)—it is therefore possible that they are able to reduce the enzyme’s protective activity. It was established that sunscreens bind to the studied enzymes mainly by alkyl, hydrogen bonds, van der Waals, π-π, π-alkyl and π-sulfur interactions. To conclude, sunscreens may become stressors affecting humans by different mechanisms and at different stages of development.